(untitled) (Journal of Computational Mathematics, 2021)
In this paper, some results about approximation in a norm S induced by the minimax series are studied. Then a Bernstein-type theorem for the norm S is established. Finally the Bernstein theorem is applied to prove the existence of certain equalities with minimax series and weighted minimax series.